(4‐Ferrocenylethyne) phenylamine on Graphene as the Signal Amplificator to Determinate Dopamine and Acetaminophen Simultaneously. Issue 6 (29th April 2013) - Wang, Linping; Liu, Meiling; Meng, Yue; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo
Abstract A novel (4‐ferrocenylethyne) phenylamine functionalized graphene sheets (FEPA‐GR), coupling with chitosan (CS) were used as a signal amplification platform for simultaneous and sensitive determination of dopamine (DA) and acetaminophen (AC). In this work, FEPA used as electron transfer mediator can be immobilized on GR surface via strong π‐π stacking interaction between the conjugate chain of FEPA and GR, which effectively prevents FEPA electron mediator leaking from the electrode surface and amplified the signal. Transmission electron microscopy, FT‐IR spectroscopy, UV‐vis spectroscopy and electrochemical experiments results are all demonstrated the strong π‐π stacking interaction between FEPA and GR. The resulted biosensor exhibited a fast response, remarkable electrocatalytic activity, perfect anti‐interference ability and good stability for simultaneous detection of DA and AC. Under the optimum conditions, the oxidation peak currents of DA and AC were linearly correlated to their concentrations in the range of 2.0–135.0 µmol·L−1 and 0.3–80.0 µmol·L−1, respectively. The lower detection limits for DA and AC were 0.30 and 0.05 µmol·L−1, respectively. The feasibility of the proposed method was validated by successfully applied to the simultaneous determination of DA and AC in serum samples with the standard addition method.